The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1021/ja00243a063
|View full text |Cite
|
Sign up to set email alerts
|

Reductive cleavage of sulfonates. Deprotection of carbohydrate tosylates by photoinduced electron transfer

Abstract: Esters of p-toluenesulfonic acid are used as protecting groups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The tosylamido chromophore has its least energetic electronic transition near 265 nm with an apparent 0–0 component at 273 nm. This corresponds to 4.54 eV, and with E (red) ∼−2.3 V for tosylamido (19) and application of the Weller equation (53) is seen to provide the excited state with more than enough driving force (over‐potential > (−) 0.7 V) for amide oxidation ( E (ox) ∼ 1.5 V [54]). Effectively, the excited tosylamido chromophore accepts an electron from the carboxamide moiety and products arise from collapse of the charge‐separated intermediate via a choice of competing pathways influenced by substrate structure.…”
Section: Resultsmentioning
confidence: 99%
“…The tosylamido chromophore has its least energetic electronic transition near 265 nm with an apparent 0–0 component at 273 nm. This corresponds to 4.54 eV, and with E (red) ∼−2.3 V for tosylamido (19) and application of the Weller equation (53) is seen to provide the excited state with more than enough driving force (over‐potential > (−) 0.7 V) for amide oxidation ( E (ox) ∼ 1.5 V [54]). Effectively, the excited tosylamido chromophore accepts an electron from the carboxamide moiety and products arise from collapse of the charge‐separated intermediate via a choice of competing pathways influenced by substrate structure.…”
Section: Resultsmentioning
confidence: 99%
“…Masanovi et al concluded that this photoreaction requires electron donors such as hydroxide or DABCO (1,4-diazabicyclo[2,2,2]octane), as shown in Chart 5. 18,19) It was generally assumed that the S-O bond of the radical anion 26…”
Section: Discussionmentioning
confidence: 99%
“…53) Effect of Electron Donor (Et 3 N) Masanovi's group and other groups reported that sulfonyl esters or sulfonamide derivatives undergo photolysis via intramolecular electron transfer 21,22,30) or intermolecular electron transfer. [18][19][20]31) As described above, the effect of substituent groups on the benzenesulfonyl moiety on the kinetics of the photolysis of 5a-d was negligible ( Table 1), indicating that intramolecular photoinduced electron transfer between two aromatic rings of 5a is a minor pathway.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations